Model Sanggit Ginem dalam Lakon Mayangkara sebagai Lakon Jenis Wejangan - Purbo Asmoro; Suwondo Suwondo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2022)
The main object of this research is to present a performance model that includes sanggit ginem in the Mayangkara show as a discourse show that contains advices in taking life so that this model can be used as a moral education for all people, especially the younger generation. Methods of creation and presentation include (1) observation to determine the gynecological vocabularies; (2) observation to compose sabet vocabularies; (3) observation to the vocal accompaniment of pakeliran; (4) observation to determine the sanggit of the show; (5) exploration of composing sanggit scenes; (5) designing a model for the sanggit gynecological discourse in the Mayangkara show; (6) the presentation of the sanggit ginem discourse in the Mayangkara show; and (7) Evaluation of the creation results. The result of the research is an applied gynecological sanggit performance of the Mayangkara show.